Appropriate Activity Assays Are Crucial for the Specific Determination of Proline Dehydrogenase and Pyrroline-5-Carboxylate Reductase Activities - Lebreton, Sandrine; Cabassa-Hourton, Cécile; Savouré, Arnould; Funck, Dietmar; Forlani, Giuseppe (Frontiers in Plant Science, 2020)
Accumulation of proline is a widespread plant response to a broad range of environmental stress conditions including salt and osmotic stress. Proline accumulation is achieved mainly by upregulation of proline biosynthesis in the cytosol and by inhibition of proline degradation in mitochondria. Changes in gene expression or activity levels of the two enzymes catalyzing the first reactions in these two pathways, namely pyrroline-5-carboxylate (P5C) synthetase and proline dehydrogenase (ProDH), are often used to assess the stress response of plants. The difficulty to isolate ProDH in active form has led several researchers to erroneously report proline-dependent NAD+ reduction at pH 10 as ProDH activity. We demonstrate that this activity is due to P5C reductase (P5CR), the second and last enzyme in proline biosynthesis, which works in the reverse direction at unphysiologically high pH. ProDH does not use NAD+ as electron acceptor but can be assayed with the artificial electron acceptor 2,6-dichlorophenol-indophenol (DCPIP) after detergent-mediated solubilization or enrichment of mitochondria. Seemingly counter-intuitive results from previous publications can be explained in this way and our data highlight the importance of appropriate and specific assays for the detection of ProDH and P5CR activities in crude plant extracts.